Research on lipoxygenase activity in natural rubber latex - Vidal P (CIRAD, 1994)
Latex was examined for a lipoxygenase, focusing primarily on the cytoplasmic serum and the lutoid serum and membranes. Lipoxygenase causes peroxidation of certain poly-unsaturated fatty acids, namely the linoleic and linolenic acids present in latex triglycerides. Lipoxygenase activity was measured using an enzymatic model, namely soya lipoxygenase, Lox-1, at various pH values. This research represents a follow-up of studies on the oxidation potentialof natural rubber.
Source Year: 1996